The role of mediodorsal thalamus in temporal differentiation of reward-guided actions - Yu, Chunxiu; Gupta, Jay; Yin, Henry H. (Frontiers in Integrative Neuroscience, 2010)
The mediodorsal thalamus (MD) is a crucial component of the neural network involved in the learning and generation of goal-directed actions. A series of experiments reported here examined the contributions of MD to the temporal differentiation of reward-guided actions. In Experiment 1, we trained rats on a discrete-trial, fixed-criterion temporal differentiation task, in which only lever presses exceeding a threshold duration value were rewarded. Pre-training MD lesions impaired temporal differentiation of action duration, by increasing the dispersion of the duration distribution. Post-training MD lesions also impaired differentiation, but by reducing the average emitted press durations, thus shifting the distribution without increasing the dispersion. In Experiment 2, we trained rats to space their lever pressing above criterion inter-press-intervals in order to earn rewards. Both pre-training and post-training MD lesions impaired the differentiation of inter-press-intervals. These results show that MD plays an important role in the acquisition and expression of action differentiation.